Corrosion-resistant titanium alloy, preparation method thereof and machining part for welding
By adding Al, Mo, Cr, Zr, Y and other elements to the titanium alloy and using multiple smelting processes to form an oxide protective film, the problem of strong corrosion of tin-silver-copper alloy on titanium alloy equipment has been solved, and the problem of tin-silver-copper alloy with high corrosion resistance on titanium alloy equipment has been significantly improved. Corrosion resistance extends equipment life and reduces maintenance costs.
Patent Information
- Application Number
- CN202310866157.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2025-01-14
AI Technical Summary
Tin-silver copper alloy has strong corrosion resistance to titanium alloy equipment, resulting in wave soldering equipment being easily corroded, short maintenance cycle and high operating costs, which affects market promotion.
Develop a corrosion-resistant titanium alloy containing 1%-8% Al, 0.5%-1.5% Mo, 0.03%-0.16% Cr, 1.5%-4.5% Zr, 0.03%-0.09% Y, by Multiple smelting processes of electron beam cold bed furnace and vacuum consumable electrode arc furnace form a stable oxide protective film, control the content of impurity elements, and improve the corrosion resistance of titanium alloy.
It significantly improves the corrosion resistance of titanium alloy, extends the service life of the equipment, reduces maintenance costs, reduces the frequency of equipment replacement, and enhances the promotion potential of the tin, silver and copper alloy ingot market.
Smart Images

Figure CN119307778A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of alloy materials, and in particular to a corrosion-resistant titanium alloy and a preparation method thereof, and processing parts for welding. Background Art
[0002] Tin-silver-copper alloy is the main raw material of solder used in wave soldering, and the components of wave soldering equipment are often made of titanium alloy. Solder has a certain corrosive effect on titanium alloy. The corrosion of tin-silver-copper alloy on titanium alloy equipment mainly includes solder erosion, acid corrosion and high temperature corrosion.
[0003] With the increasing number of wave soldering equipment, the corrosion resistance of wave soldering equipment has received more and more attention. Tin-silver-copper alloy is highly corrosive to titanium alloy parts of wave soldering equipment, which seriously affects the market promotion of tin-silver-copper alloy ingots. At present, the surface corrosion of the corrosive parts of wave soldering equipment is serious, resulting in a short maintenance cycle and high wave soldering operation costs. Therefore, the development of corrosion-resistant titanium alloys suitable for wave soldering has great practical significance. Summary of the invention
[0004] The main purpose of the present application is to provide a corrosion-resistant titanium alloy and a preparation method thereof, and processing parts for welding, aiming to solve the technical problem that titanium alloy parts have poor corrosion resistance to tin-silver-copper solder.
[0005] To achieve the above-mentioned purpose, an embodiment of the present application provides a corrosion-resistant titanium alloy, which includes, by mass percentage, 1%-8% Al, 0.5%-1.5% Mo, 0.03%-0.16% Cr, 1.5%-4.5% Zr, 0.03%-0.09% Y, and the remainder is Ti and impurity elements, and the Fe content of the impurity elements is less than or equal to 0.15%.
[0006] The present application also provides a method for preparing a corrosion-resistant titanium alloy, which is used to prepare the corrosion-resistant titanium alloy as described above. The preparation method comprises the following steps:
[0007] Using TA0 industrial pure titanium with Fe content less than 0.02%, double zero-grade electrolytic aluminum ingots, Ti-40% Mo master alloy, Ti-30% Cr master alloy, Al-10% Zr master alloy, Ti-3% Y master alloy as raw materials, pretreating the raw materials;
[0008] The pre-treated raw materials were put into the electron beam cooling furnace for smelting according to the mass percentage, and the ingot pulling speed was controlled at 0.9×10 -4 m / s-1.1×10 -4 m / s, the pressure in the furnace is controlled at 0.2Pa-0.5Pa, and a primary ingot is obtained;
[0009] The primary ingot is used as a raw material, and secondary smelting is performed in a vacuum consumable electrode arc furnace to obtain the corrosion-resistant titanium alloy ingot.
[0010] The embodiment of the present application further provides a processing component for welding, wherein the material of the processing component for welding is the corrosion-resistant titanium alloy as described above.
[0011] The embodiment of the present application discloses a corrosion-resistant titanium alloy, which includes, by mass percentage, 1%-8% Al, 0.5%-1.5% Mo, 0.03%-0.16% Cr, 1.5%-4.5% Zr, 0.03%-0.09% Y, and the remainder is Ti and impurity elements, wherein the content of Fe in the impurity elements is less than or equal to 0.15%. By adding alloying elements Al, Mo, Cr, and Zr, a stable, firm, and dense Al 2 O 3 Cr 2 O 3 、Mo 2 O 3 、TiO 2 And inert oxide protective films such as ZrO protect the titanium alloy matrix. The alloy structure is refined by adding rare earth element Y. In addition, the content of impurity elements in the alloy is strictly controlled. Under the synergistic effect of various elements, the corrosion resistance of titanium alloy is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a schematic flow chart of a method for preparing a corrosion-resistant titanium alloy according to an embodiment of the present application.
[0013] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0014] It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0015] The corrosion mechanism of tin-silver-copper alloy on titanium alloy includes: (1) solder corrosion: under dynamic high-temperature solder corrosion, Sn and its oxides will react with Fe in titanium alloy, while alkaline oxides such as Cd and Pb in solder will dissolve with titanium; (2) acid corrosion: due to the action of acidic oxides in flux and solder (rosin acid, Pb 2 O 5) etc. Titanium is prone to acid corrosion; (3) High temperature corrosion: Titanium alloys are very active at high temperatures, with high oxygen, carbon and nitrogen content. Above 500°C, they easily react with oxygen, carbon and nitrogen. In scenarios where electronic products are processed by wave soldering, selective soldering, module soldering, etc. where titanium alloy parts are in contact with tin baths, the titanium alloy parts will undergo the above corrosion mechanism, resulting in corrosion of the parts, requiring shutdown for maintenance and equipment replacement. Due to the above corrosion mechanism, titanium alloy parts undergo dissolution, resulting in a reduction in service life.
[0016] To solve the above technical problems, an embodiment of the present application provides a corrosion-resistant titanium alloy. In terms of mass percentage, the corrosion-resistant titanium alloy includes 1%-8% Al, 0.5%-1.5% Mo, 0.03%-0.16% Cr, 1.5%-4.5% Zr, 0.03%-0.09% Y, and the remainder is Ti and impurity elements, and the Fe content among the impurity elements is less than or equal to 0.15%.
[0017] Titanium alloy has the characteristics of high strength and good heat resistance, and can be used as an impeller in wave soldering equipment. The Fe element in titanium alloy is one of the causes of corrosion. Therefore, in the embodiment of the present application, on the basis of controlling the Fe element content to maintain a low level, other alloying elements are added to improve the corrosion resistance of titanium alloy in the tin bath processing scenario.
[0018] The matrix titanium metal in titanium alloy has two allomorphous crystals: close-packed hexagonal (α phase) and body-centered cubic (β phase). α titanium alloy is a single-phase alloy composed of α phase solid solution, with strong oxidation resistance, but cannot be strengthened by heat treatment and has low room temperature strength. β titanium alloy is a single-phase alloy composed of β phase solid solution, which has high strength without heat treatment, but has poor thermal stability and is not suitable for use at high temperatures. α+β two-phase alloy has good comprehensive performance and good organizational stability.
[0019] 1.0%-8.0% Al is added to the corrosion-resistant titanium alloy, such as 1.0%, 3.0%, 5.0%, 7.0%, 8.0%, etc. Al is an α (Ti) stabilizing element, which can not only dissolve in the α phase in large quantities to improve the strength of the alloy, but also form Al on the surface of the titanium alloy. 2 O 3 Thin film. Al 2 O 3 It is a ceramic coating with good density and non-wetting with Sn, so it is resistant to corrosion by liquid SAC305 alloy. SAC305 alloy refers to a solder containing about 3% Ag, about 0.5% Cu, and the balance Sn. It is a very widely used solder for wave soldering. For example, the Al content can be 4%-6%. The increase in Al content may lead to brittle Ti 3The formation of Al phase leads to a decrease in the strength of the alloy. Therefore, adding an appropriate amount of Al can maintain the strength of the alloy while improving the corrosion resistance.
[0020] Adding 0.5%-1.5% Mo to the corrosion-resistant titanium alloy, such as 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, etc., the Mo element can be infinitely soluble in β (Ti) at high temperature, and is a β isomorphous stabilizing element, which can improve the structural stability of the alloy and the corrosion resistance of the alloy. Exemplarily, the Mo content is 0.5%-0.8%. Among the β isomorphous stabilizing elements, the strengthening effect of the Mo element is the most obvious, which can improve the room temperature and high temperature strength of the alloy.
[0021] 0.03%-0.16% Cr is added to the corrosion-resistant titanium alloy, for example, 0.03%, 0.06%, 0.09%, 0.12%, 0.16%, etc. Cr is a stabilizing element of the eutectoid β (Ti), which can expand the β (Ti) phase region and improve the alloy processing performance and organizational stability. Exemplarily, the Cr content is 0.05%-0.08%. The Cr element can cause eutectoid transformation, and the eutectoid reaction temperature with titanium is low and the transformation speed is slow. The alloy with the addition of Cr has high strength and good plasticity, and can be strengthened by heat treatment. Controlling the content of the Cr element within a suitable range can avoid the precipitation of compounds and reduce plasticity.
[0022] Adding 1.5%-4.5% Zr to the corrosion-resistant titanium alloy, for example, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, the Zr element can be infinitely miscible with the α (Ti) phase and the β (Ti) phase, and can delay harmful phase transformations in the alloy, thereby improving the corrosion resistance and mechanical strength of the titanium alloy. In the titanium alloy system, there are many types of phase transformations that may occur, and the addition of alloying elements will affect the phase transformation temperature and phase structure, some of which affect the corrosion resistance and strength properties of the alloy, and such phase transformations can be regarded as harmful phase transformations. Exemplarily, the Zr content is 3.5%-4.0%. The Zr element has little effect on the β transformation temperature and is a neutral element. The Zr element has a strong high-temperature strengthening effect on the alloy, which is beneficial for the titanium alloy to work in a temperature environment of 260-270°C.
[0023] 0.03-0.09% of rare earth element Y is added to the corrosion-resistant titanium alloy, such as 0.03%, 0.05%, 0.07%, 0.09%, etc. Rare earth element Y can purify the alloy and refine the grains, and can capture the interstitial oxygen in the alloy matrix to form Y 2 O 3 , eliminating the harmful effects of impurity oxygen, etc., thereby improving the corrosion resistance of titanium alloy. Exemplarily, the content of Y element is 0.05%-0.06%. Adding a small amount of Y can improve the high temperature oxidation resistance of titanium alloy.
[0024] In addition to Fe, impurity elements may also include N, H and O, and the total amount of impurity elements may be controlled to be less than or equal to 0.15%. For example, the Fe content in the corrosion-resistant titanium alloy is less than or equal to 0.02%, the N content is less than or equal to 0.02%, the H content is less than or equal to 0.015%, and the O content is less than or equal to 0.05%. Among them, N, H and O elements are relatively common impurity elements in titanium alloys, and the purpose of reducing the impurity content can be achieved by controlling environmental conditions. N and O are α-stable elements, which can increase the strength of titanium alloys, but the plasticity will drop sharply. The solubility of H element in α phase decreases with decreasing temperature. When cooled to room temperature, brittle hydrides are easily precipitated, resulting in hydrogen embrittlement. Therefore, the content of H element should be strictly controlled. As for Fe element, in the tin bath processing scenario, Sn and oxides will react with Fe in titanium alloy, so the Fe content has a greater impact on the corrosion resistance of titanium alloy, and should also be strictly controlled at a low level. The content of impurity elements can also be controlled through the selection of raw materials. For raw materials from different origins and using different preparation processes, there will be certain differences in the impurity content. Selecting raw materials with low impurity content can achieve the effect of controlling the content of impurity elements in titanium alloys.
[0025] The corrosion-resistant titanium alloy prepared in the embodiment of the present application is an α+β two-phase alloy. For the two-phase α+β alloy, increasing the content of β-stabilizing elements in the alloy is an effective method to improve the strength of the alloy. A sufficient amount of β-stabilizing elements can play a role in solid solution strengthening, expand the β phase region, and retain more β phase and metastable β phase. The metastable β phase can precipitate a strengthening phase during the subsequent aging treatment, thereby improving the strength of the alloy. The alloy element composition and content ratio provided in the embodiment of the present application are adopted to improve the corrosion resistance of the titanium alloy through multiple means such as multi-component composite alloying, alloy purification, solid solution strengthening, and fine grain strengthening of the alloy. By adding elements such as Al, Mo, Co, Cr, Zr, and Y, a stable, firm, and non-dynamic Al is formed on the surface of the alloy. 2 O 3 Cr 2 O 3 、Mo 2 O 3 、TiO 2 , ZrO and other inert oxide protective films to improve the corrosion resistance of titanium alloys.
[0026] The present invention provides a method for preparing a corrosion-resistant titanium alloy. Figure 1 , Figure 1 This is a schematic flow chart of an embodiment of a method for preparing a corrosion-resistant titanium alloy of the present application.
[0027] In this embodiment, the preparation method of the corrosion-resistant titanium alloy includes:
[0028] Step S10, using TA0 industrial pure titanium with an Fe content of less than 0.02%, double zero-grade electrolytic aluminum ingots, Ti-40% Mo master alloy, Ti-30% Cr master alloy, Al-10% Zr master alloy, and Ti-3% Y master alloy as raw materials, pre-treating the raw materials;
[0029] TA0 industrial pure titanium is an industrial pure titanium grade that meets the GB / T3620.1 standard, with iron not exceeding 0.15%, carbon not exceeding 0.10%, nitrogen not exceeding 0.03%, hydrogen not exceeding 0.015%, oxygen not exceeding 0.15%, other single elements less than 0.1%, and the total not exceeding 0.4%, and the remainder is titanium. The embodiment of the present application further limits the Fe content in TA0 industrial pure titanium, requiring the use of TA0 industrial pure titanium with an Fe content of less than 0.02%, controlling the content of Fe impurities in the titanium alloy from the selection of raw materials, and elements such as Mo, Co, Cr, Zr, and Y are all added in the form of intermediate alloys.
[0030] The step of pretreating the raw materials may include: shearing the double zero-grade electrolytic aluminum ingots into blocks with a particle size of 2-5mm, for example, the block size is 2mm, 3mm, 4mm, 5mm, etc., crushing and screening the Ti-40% Mo master alloy, Ti-30% Cr master alloy, Ti-50% Zr master alloy, Ti-3% Y master alloy into blocks with a particle size of 3-8mm, for example, the block size is 3mm, 5mm, 7mm, 8mm, etc.; drying the blocks.
[0031] The aluminum ingot and the master alloy are made into blocks of smaller particle size, which is convenient for controlling the amount of alloy elements added during batching and fully mixing the alloy elements and Ti elements during smelting. The raw materials can be placed in a drying furnace to dry and remove the moisture adsorbed in the raw materials.
[0032] Step S20, the pre-treated raw materials are put into the electron beam cooling furnace for smelting according to the mass percentage, and the ingot pulling speed is controlled at 0.9×10 -4 m / s-1.1×10 -4 m / s, the pressure in the furnace is controlled at 0.2Pa-0.5Pa, and a primary ingot is obtained;
[0033] The electron beam cooling hearth furnace is a device that uses electron beams to bombard raw materials and combines cold bed smelting and impurity removal. The raw materials enter the vacuum chamber through the feeding system, the electron beam melts the raw materials, and a molten pool is gradually established in the cold bed. Refining is carried out in the refining area of the cold bed. As the melting process progresses, the liquid level of the cold bed molten pool rises, and the molten liquid metal flows into the crystallizer. The ingot head in the ingot pulling system is continuously pulled down to obtain a primary ingot with a preset shape and size. The ingot pulling speed is adapted to the melting speed of the raw materials, so that the formed primary ingot can maintain the preset shape and size. The raw materials are bombarded by high-density electron beams to form a molten pool, high-density impurities sink to the bottom of the molten pool, and low-density impurities float on the surface of the molten pool. The impurities that cannot be melted or dissolved in the alloy can be removed by flotation and sedimentation. By controlling the furnace pressure, the burnout of the alloying element aluminum can also be reduced, and a primary ingot with a higher purity can be obtained.
[0034] Step S30, using the primary ingot as a raw material, performing secondary smelting in a vacuum consumable electrode arc furnace to obtain an ingot of corrosion-resistant titanium alloy.
[0035] The vacuum consumable electrode arc furnace adopts the vacuum consumable principle. The molten material is used as one electrode and the water-cooled copper crucible is used as the other electrode. An arc is struck between the two electrodes. The molten material is melted by the high temperature of the arc and drips into the crucible, gradually melting and condensing into ingots. The melting and condensation speeds in the vacuum consumable smelting process are relatively fast. The smelted ingots usually have the advantages of uniform composition and less segregation, and hydrogen and some volatile impurities can be removed. The corrosion-resistant titanium alloy ingots that have undergone secondary smelting have the advantages of very low inclusions of gas and low-melting-point impurities, and effective removal of high-density and low-density inclusions.
[0036] In this embodiment, high-quality raw materials with low impurity content are selected to reduce the introduction of impurities from the source, and an electron beam cooling hearth furnace is used for primary smelting, and a vacuum consumable electrode arc furnace is used for secondary smelting. The advantages of different smelting methods are used to remove impurities in the alloy to prepare high-quality ingots. The alloy is made into parts that directly contact with soldering in welding equipment, thereby improving the soldering corrosion resistance in a working environment of 260-270°C, extending the service life of the parts, reducing the frequency of equipment replacement, and saving the operation and maintenance costs of the welding equipment.
[0037] The embodiments of the present application also provide a processing component for welding, and the material of the processing component is the corrosion-resistant titanium alloy disclosed in the above embodiments. This processing component can be an impeller, which is arranged inside the tin bath of wave soldering, selective soldering, module soldering and other equipment. Taking wave soldering equipment as an example, the molten liquid solder needs to be pumped to form a solder wave of a specific shape on the solder liquid surface, and the electronic products with components inserted are placed on the conveyor chain, and the solder points are welded by passing through the solder wave at a specific angle and a certain immersion depth. The rotation of the impeller can help the formation of the wave. During the processing, the processing component made of corrosion-resistant titanium alloy is in direct contact with the tin solder. Due to the extremely low content of impurity Fe elements and the addition of Al, Mo, Co, Cr, Zr, Y and other elements, a stable, firm, and non-dynamic Al can be formed on the surface of the alloy. 2 O 3 Cr 2 O 3 、Mo 2 O 3 、TiO 2 , ZrO and other inert oxide protective films, so the processed parts can resist solder corrosion. And the improvement of corrosion resistance of processed parts can also reduce downtime for maintenance, improve equipment utilization, reduce the frequency of spare parts replacement, and save spare parts procurement costs.
[0038] In order to better illustrate the technical solutions of the embodiments of the present application, the composite solder and the preparation method of the composite solder provided by the present application are further explained in combination with several embodiments below.
[0039] Example 1
[0040] Ingredients are prepared according to the following mass percentages:
[0041] Ti+1%Al+1.5%Mo+0.12%Cr+1.5%Zr+0.03%Y, impurity elements Fe≤0.02%, N≤0.02%, H≤0.015%, O≤0.05%, the total amount of impurity elements in the alloy is not more than 0.15%.
[0042] The raw materials used are TA0 industrial pure titanium with Fe content less than 0.02%, double zero-grade electrolytic aluminum ingots, Ti-40% Mo master alloy, Ti-30% Cr master alloy, Al-10% Zr master alloy, and Ti-3% Y master alloy.
[0043] The raw materials are put into the electron beam cooling furnace for smelting, and the ingot pulling speed is controlled at 0.9×10 -4 m / s-1.1×10 -4m / s, the pressure in the furnace is controlled at 0.2Pa-0.5Pa, and a primary ingot is obtained; the primary ingot is used as a raw material, and secondary smelting is carried out in a vacuum consumable electrode arc furnace to obtain an ingot of corrosion-resistant titanium alloy; the ingot is processed into a titanium alloy impeller.
[0044] Example 2
[0045] Ingredients are prepared according to the following mass percentages:
[0046] Ti+8%Al+0.5%Mo+0.03%Cr+4.5%Zr+0.09%Y, impurity elements Fe≤0.02%, N≤0.02%, H≤0.015%, O≤0.05%, the total amount of impurity elements in the alloy is not more than 0.15%.
[0047] The raw materials used are TA0 industrial pure titanium with Fe content less than 0.02%, double zero-grade electrolytic aluminum ingots, Ti-40% Mo master alloy, Ti-30% Cr master alloy, Al-10% Zr master alloy, and Ti-3% Y master alloy.
[0048] The raw materials are put into the electron beam cooling furnace for smelting, and the ingot pulling speed is controlled at 0.9×10 -4 m / s-1.1×10 -4 m / s, the pressure in the furnace is controlled at 0.2Pa-0.5Pa, and a primary ingot is obtained; the primary ingot is used as a raw material, and secondary smelting is carried out in a vacuum consumable electrode arc furnace to obtain an ingot of corrosion-resistant titanium alloy; the ingot is processed into a titanium alloy impeller.
[0049] Example 3
[0050] Ingredients are prepared according to the following mass percentages:
[0051] Ti+5%Al+0.8%Mo+0.16%Cr+3%Zr+0.05%Y, impurity elements Fe≤0.02%, N≤0.02%, H≤0.015%, O≤0.05%, the total amount of impurity elements in the alloy is not more than 0.15%.
[0052] The raw materials used are TA0 industrial pure titanium with Fe content less than 0.02%, double zero-grade electrolytic aluminum ingots, Ti-40% Mo master alloy, Ti-30% Cr master alloy, Al-10% Zr master alloy, and Ti-3% Y master alloy.
[0053] The raw materials are put into the electron beam cooling furnace for smelting, and the ingot pulling speed is controlled at 0.9×10 -4 m / s-1.1×10 -4m / s, the pressure in the furnace is controlled at 0.2Pa-0.5Pa, and a primary ingot is obtained; the primary ingot is used as a raw material, and secondary smelting is carried out in a vacuum consumable electrode arc furnace to obtain an ingot of corrosion-resistant titanium alloy; the ingot is processed into a titanium alloy impeller.
[0054] Example 4
[0055] Ingredients are prepared according to the following mass percentages:
[0056] Ti+2.8%Al+0.65%Mo+0.08%Cr+2.5%Zr+0.07%Y, impurity elements Fe≤0.02%, N≤0.02%, H≤0.015%, O≤0.05%, the total amount of impurity elements in the alloy is not more than 0.15%.
[0057] The raw materials used are TA0 industrial pure titanium with Fe content less than 0.02%, double zero-grade electrolytic aluminum ingots, Ti-40% Mo master alloy, Ti-30% Cr master alloy, Al-10% Zr master alloy, and Ti-3% Y master alloy.
[0058] The raw materials are put into the electron beam cooling furnace for smelting, and the ingot pulling speed is controlled at 0.9×10 -4 m / s-1.1×10 -4 m / s, the pressure in the furnace is controlled at 0.2Pa-0.5Pa, and a primary ingot is obtained; the primary ingot is used as a raw material, and secondary smelting is carried out in a vacuum consumable electrode arc furnace to obtain an ingot of corrosion-resistant titanium alloy; the ingot is processed into a titanium alloy impeller.
[0059] The comparative example is TA0 alloy of Vanadium Titanium Co., Ltd.
[0060] The corrosion resistance test was conducted on the tin-silver-copper alloy corrosion-resistant titanium alloy of the above-mentioned Examples 1-4 and the conventional TA0 titanium alloy of the comparative example. The titanium alloy impellers of the materials of Examples 1-4 and the comparative example were placed in a wave soldering accelerated corrosion tester at 280°C for 500 hours to measure the corrosion rate. The specific experimental results are shown in Table 1.
[0061] Table 1
[0062]
[0063] Corrosion rate = (original weight - remaining weight) / original weight, the higher the corrosion rate, the worse the corrosion resistance. As can be seen from Table 1, compared with the conventional TA0 titanium alloy in the comparative example, the corrosion resistance of the tin-silver-copper alloy corrosion-resistant titanium alloys in Examples 1-4 is significantly improved.
[0064] The serial numbers of the above-mentioned embodiments of the present application are for description only and do not represent the advantages or disadvantages of the embodiments.
[0065] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A corrosion-resistant titanium alloy, characterized in that: Measured in mass percentage, the corrosion-resistant titanium alloy includes 1%-8% Al, 0.5%-1.5% Mo, 0.03%-0.16% Cr, 1.5%-4.5% Zr, 0.03%-0.09% Y, and the remainder is Ti and impurity elements, and the content of Fe in the impurity elements is less than or equal to 0.15%.
2. The corrosion-resistant titanium alloy according to claim 1, characterized in that: The Al content in the corrosion-resistant titanium alloy is 4%-6%.
3. The corrosion-resistant titanium alloy according to claim 1, characterized in that: The content of Mo in the corrosion-resistant titanium alloy is 0.5%-0.8%.
4. The corrosion-resistant titanium alloy according to claim 1, characterized in that: The Cr content in the corrosion-resistant titanium alloy is 0.05%-0.08%.
5. The corrosion-resistant titanium alloy according to claim 1, characterized in that: The Zr content in the corrosion-resistant titanium alloy is 3.5%-4.0%.
6. The corrosion-resistant titanium alloy according to claim 1, characterized in that: The Y content in the corrosion-resistant titanium alloy is 0.05%-0.06%.
7. The corrosion-resistant titanium alloy according to any one of claims 1 to 6, characterized in that: The Fe content in the corrosion-resistant titanium alloy is less than or equal to 0.02%, the N content is less than or equal to 0.02%, the H content is less than or equal to 0.015%, and the O content is less than or equal to 0.05%.
8. A method for preparing a corrosion-resistant titanium alloy, characterized in that: For preparing the corrosion-resistant titanium alloy according to any one of claims 1 to 7, the preparation method comprises the following steps: Using TA0 industrial pure titanium with Fe content less than 0.02%, double zero-grade electrolytic aluminum ingots, Ti-40% Mo master alloy, Ti-30% Cr master alloy, Al-10% Zr master alloy, Ti-3% Y master alloy as raw materials, pretreating the raw materials; The pre-treated raw materials were put into the electron beam cooling furnace for smelting according to the mass percentage, and the ingot pulling speed was controlled at 0.9×10 -4 m / s-1.1×10 -4 m / s, the pressure in the furnace is controlled at 0.2Pa-0.5Pa, and a primary ingot is obtained; The primary ingot is used as a raw material, and secondary smelting is performed in a vacuum consumable electrode arc furnace to obtain the corrosion-resistant titanium alloy ingot.
9. The method for preparing the corrosion-resistant titanium alloy according to claim 8, characterized in that: The step of pre-treating the raw material comprises: The double zero-grade electrolytic aluminum ingot is sheared into blocks with a particle size of 2-5 mm, and the Ti-40% Mo master alloy, Ti-30% Cr master alloy, Al-10% Zr master alloy, and Ti-3% Y master alloy are crushed and screened into blocks with a particle size of 3-8 mm; The block is dried.
10. A processing component for welding, characterized in that: The material of the welding processing part is the corrosion-resistant titanium alloy according to any one of claims 1 to 7.